Radar Observations of Arctic Bird Migration in the Beringia Region - Hedenström, Anders; Alerstam, Thomas; Bäckman, Johan; Gudmundsson, G. A.; Henningsson, Sara; Karlsson, Håkan; Rosén, Mikael; Strandberg, Roine (The Arctic Institute of North America, 2009)
Bird migration was recorded by tracking radar and visual observations in the Beringia region. The data were subdivided into seven areas extending from north of Wrangel Island southeastward toward the Bering Strait and then northwestward off the coast of Alaska to Point Barrow. The studies, which took place during a ship-based expedition between 30 July and 19 August 2005, recorded a total of 557 tracks (average duration 120 seconds) of bird flocks or individuals on post-breeding migration. The dominant eastward-flying flocks were likely composed of shorebirds on their way from breeding areas in central or eastern Siberia to intermediate stopovers and final destinations in North and South America. The courses were more southerly into the Bering Strait, possibly because of topographical influence. At two areas, the Chukchi Sea and Koluchinskaya Bay, there was also a westward component of migrants. At the Chukchi Sea these were almost certainly passerine birds migrating from Alaska to wintering areas in Asia and Africa, while at Koluchinskaya Bay, king ciders on molt migration could represent an important part of the westward component. The overall mean altitude of flights was 1157 m, and flight altitude was positively correlated with latitude. The mean ground speed was 15.9 m/s and the mean airspeed was 14.1 m/s, indicating that on average the birds were experiencing a small tail wind component. The airspeed was a function of the tail wind component and the vertical speed; altitude and the side wind component did not contribute significantly to variation in airspeed in this data set. Comparing these results with similar data obtained from Siberia and Canada, we concluded that Beringia is a migration hotspot where intense bird migration crosses between Asia and Alaska in both directions.